Post-truth strategies and disinformation in the 2022 Colombian presidential elections - Gutiérrez-Coba, Liliana (2023)
Mis/disinformation and post-truth discourses are part of contemporary public communication. The aim is to identify the politicians' discursive strategies and those who want to discredit them through false or inaccurate content circulating on social networks and other media. In particular, the analysis focuses on the 2022 presidential elections in Colombia. The specific objectives were: to establish the formal characteristics of the false or imprecise messages that refer to or were attributed during the campaign to the candidates Gustavo Petro, from the Pacto Histórico party, and Rodolfo Hernández, from the Movement of Anti-Corruption Governors, determine the semantic orientation of these messages and identify the types of fallacies used in their production. For this purpose, we developed content and sentiment analysis on the messages verified by fact-checkers between January and June 2022. The findings contribute to a better understanding of the post-truth strategies used by candidates and malicious agents to generate emotional responses in voters. The results revealed a prominent sentiment of negativity associated with disinformation discourse, which serves to attack, discredit, and delegitimize political contenders through especially fear-based fallacies.